2011
DOI: 10.2147/opth.s27324
|View full text |Cite
|
Sign up to set email alerts
|

Visual performance of the Tecnis one-piece lens ZCB00

Abstract: SynopsisThe aspheric, one-piece design of the Tecnis® ZCB00 intraocular lens provided higher mesopic contrast sensitivity and relatively constant refraction at different pupil sizes compared to the Sensar® AR40e.PurposeComparing the impact on functional vision of the aspheric Tecnis® ZCB00 one-piece lens compared to the spherical Sensar® AR40e three-piece lens.SettingNational Eye Hospital, Cairo, Egypt.MethodsIn this prospective study, we implanted 32 Tecnis ZCB00 (Abbott Medical Optics, Santa Ana, CA) and 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…In this study an aspheric surface as a possible best-fit surface was proposed to ascertain whether IOL surface designs are spherical, aspherical, or higher-order aspherical. As consequence of this new approach, this study confirmed that the anterior surface of the Tecnis 1 IOL was aspherical and the second one was spherical as several reports have stated 12 , 14 , 15 but not showed (see Fig. 4 A–C).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study an aspheric surface as a possible best-fit surface was proposed to ascertain whether IOL surface designs are spherical, aspherical, or higher-order aspherical. As consequence of this new approach, this study confirmed that the anterior surface of the Tecnis 1 IOL was aspherical and the second one was spherical as several reports have stated 12 , 14 , 15 but not showed (see Fig. 4 A–C).…”
Section: Discussionsupporting
confidence: 86%
“…Tecnis 1 ZCB00 IOL (Johnson & Johnson Vision, Inc), is a monofocal biconvex IOL with spherical posterior surface and an anterior aspheric surface that provided a negative SA of − 0.27 μm in an optical zone of 6 mm 12 , 14 , 15 .…”
Section: Methodsmentioning
confidence: 99%
“…e w 13 better, statistically significant DCVA than the Clareon® IOL. Our VA outcomes for the TECNIS® ZCB00 IOL are in line with those reported by other authors (15)(16)(17). On the contrary, the result we obtained for DCVA in the Clareon® IOL group (0.05 Some parameters can help us correlate the patient's perception (i.e., visual quality) with the eye's optical quality : OSI, MTF, SR or LCA.…”
supporting
confidence: 91%
“… 9 Especially in context to the present study, where the monofocal IOL implanted was the aspheric and chromatic aberration correcting Tecnis-1 IOL; which is already shown to deliver excellent contrast after cataract surgery. 21 Both the IOLs, being manufactured on the same platform, when implanted together in contralateral eyes result in excellent quality of vision post-op.…”
Section: Discussionmentioning
confidence: 99%